FORMULASI BAHAN DASAR LENGKAP LARUTAN PENGAWET BUNGA POTONG KRISAN (Dendranthema indicum) - Farida Iriani (Jurnal Agroekoteknologi, 2009)
ABSTRACTThe quality of cut flowers can be improved by soaking them in a preservative solution, containing three basic compounds, sucrose, citric acid, and Lysol (called the basic formula). A research was conducted to find out an exact formulation which can give an optimal result by mixing the basic formula with cytocinine as a growth substances or anti-ethylene molecule as an completing agent (called the complete basic formula) for chrysanthemum cut flower. This research was done in the plant physiology laboratorium at Faculty of Agriculture of Bandung Raya University, Bandung on July to August 2004 by using univariat Randomized Block Design method consists five treatments, which are basic formula, basic formula + cynetine, basic formula + BAP, basic formula + AOA, and basic formula + STS. The result shows that the quality of chrysanthemum cut flowers can be kept by soaking it in a basic formulation preservative solution only, which containts 48 x 103 mgL-1 sucrose + 241 mgL-1 citric acid + 800 mgL-1 lysol in 14 hours. Soaking the cut flowers in a preservative solution, the decreasing of fresh weight is also minimalized and relative 2-days water uptake is maximalized. The number of ethylene that synthesized and respiration activity of chrysanthemum cut flowers can be pushed by adding the cytocinine into basic formula. Key Words:  Preservative Solution, Quality Of Chrysanthemum Flowers, Growth Substances Cytocinine, Anti-Ethylene